RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA KARYAWAN MENGGUNAKAN METODE ANALYTICAL HIERARCHI PROCESS (AHP) - Rohmat Taufik (Faktor Exacta, 2011)
The performance appraisal is important for every employee and is useful for companies to define the next policy action. In RS Roemani performance ppraisal is used to process a promotion, performance evaluation, Haj subsidy, employee certificates of achievement and adjustment, while the criteria used by 4 criteria and 13 sub criteria and their implementation is still done_by_hand. The method used in this study using the Analytical Hierarchy Process (AHP) due to a complex problem can be easily simplified to speed up decision-making process by way of preparation of the hierarchy, giving the comparative value of each criterion to determine a value criteria. The criteria used are considered honest commitment, loyalty, responsibility and discipline. Management assessed in management leadership, planning, organizing and directing. Cooperation is considered communications, adapt and share information. The work is judged is the quality and quantity. Performance appraisal decision support system designed by using AHP method can be used for all the assessment process while determining the criteria and sub criteria can change in accordance with management agreements. Keywords: Decision Support Systems, AHP, Performance Appraisal